A Replication of Jones & Marinescu (2022) - Etienne Bacher; Mario Herrera-Rodriguez; Diego Marino Fages; Felix Stips (Institute for Replication (I4R), 2023)
Jones and Marinescu (2022) study the employment effects of a universal cash transfer in Alaska. Using a synthetic control method, they find that the transfer had no negative effects on employment. We reproduce the results using their replication package and investigate if the results hold when using a different software to run the analysis. We also use different estimation techniques and perform sensitivity checks to assess robustness of the results. We find some differences in the size and significance of the average treatment effects on labor force participation and hours worked when we use a different software (R) and various extensions of the synthetic control method. We also find smaller coefficients on part-time employment when including more covariates. However, these differences do not contradict the main conclusion of the paper.
Keywords: 330; synthetic control; labour market; universal cash transfer; replication